2002
DOI: 10.1080/00365540110080052
|View full text |Cite
|
Sign up to set email alerts
|

Free-living Amoebae Promote Growth and Survival of Helicobacter pylori

Abstract: Transmission routes of Helicobacter pylori remain poorly understood. The finding of bacterial DNA in water suggests the involvement of environmental factors. Here we report successful co-cultivation of H. pylori with Acanthamoeba castellanii, which circumvents the requirement of this bacterium for precise microaerobic conditions and a large supply of nutrients in order to grow. H. pylori was able to propagate and remain viable for several weeks in the presence of amoebae under experimental conditions. Intact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 4 publications
4
81
0
Order By: Relevance
“…Amoebae feed on mixed communities of bacteria within biofilms including, pathogenic bacteria such as species of Legionella, Mycobacterium, P. aeruginosa, Vibrio cholerae, Helicobacter pylori [6,12,45,46,59]. Once inside the amoebal cell, some bacteria will survive or escape the adverse conditions presented by digestive vacuoles, but can also find sanctuary from unfavourable environmental conditions and can multiply [25].…”
mentioning
confidence: 99%
“…Amoebae feed on mixed communities of bacteria within biofilms including, pathogenic bacteria such as species of Legionella, Mycobacterium, P. aeruginosa, Vibrio cholerae, Helicobacter pylori [6,12,45,46,59]. Once inside the amoebal cell, some bacteria will survive or escape the adverse conditions presented by digestive vacuoles, but can also find sanctuary from unfavourable environmental conditions and can multiply [25].…”
mentioning
confidence: 99%
“…It has also been suggested that H. pylori may survive in water distribution networks by becoming associated with autochthonous microorganisms present in biofilms formed in such systems (5,18,29). Park et al (22) reported the detection of H. pylori for the first time in drinking water biofilms taken from a public water distribution system.…”
mentioning
confidence: 99%
“…There is only one published study about the interactions between H. pylori and amoebae [23]. In this paper, the authors showed that H. pylori was able to survive within trophozoites of Acanthamoeba castellanii under experimental conditions.…”
Section: H Pylorimentioning
confidence: 71%
“…Although further research regarding bacteriaamoeba interactions is necessary, the current knowledge for all bacteria present in the CCL [7,13,23,26,30,41,49] indicates that amoebae could play a key role in bacterial resistance to disinfection, and survival and spread in drinking water systems. Additionally, bacteria-amoeba interactions suggest that, after a contamination episode, the presence of fecal-related pathogens, such as C. jejuni, E. coli O157:H7, H. pylori, S. enterica and S. sonnei, could not be detected using only conventional fecal indicators, as some enteric bacterial pathogens may survive within a moebae and still be present at lower concentrations.…”
Section: Discussionmentioning
confidence: 99%